Tezacaftor/Ivacaftor in Subjects with Cystic Fibrosis and F508del/F508del-CFTR or F508del/G551D-CFTR. - Donaldson,SH; Pilewski,JM; Griese,M; Cooke,J; Viswanathan,L; Tullis,E; Davies,JC; Lekstrom-Himes,JA; Wang,LT; VX11-661-101,Study Group (American Journal of Respiratory and Critical Care Medicine, 2017)
RATIONALE: Tezacaftor (formerly VX-661) is an investigational small molecule that improves processing and trafficking of the cystic fibrosis transmembrane conductance regulator (CFTR) in vitro, and improves CFTR function alone and in combination with ivacaftor. OBJECTIVES: To evaluate safety and efficacy of tezacaftor monotherapy and tezacaftor/ivacaftor combination therapy in subjects with CF homozygous for F508del or compound heterozygous for F508del and G551D. METHODS: This was a randomized, placebo-controlled, double-blind, multicenter, phase 2 study (NCT01531673). Subjects homozygous for F508del received tezacaftor (10 mg to 150 mg) qday alone or in combination with ivacaftor 150 mg q12h in a dose escalation phase, as well as in a dosage regimen testing phase. Subjects compound heterozygous for F508del and G551D taking physician prescribed ivacaftor received tezacaftor 100 mg qday. MEASUREMENTS AND MAIN RESULTS: Primary endpoints were safety through day 56 and change in sweat chloride from baseline through day 28. Secondary endpoints included change in percent predicted FEV1 (ppFEV1) from baseline through day 28 and pharmacokinetics. The incidence of adverse events was similar across treatment arms. Tezacaftor 100 mg qday/ivacaftor 150 mg q12h resulted in a 6.04 mmol/L decrease in sweat chloride and 3.75 percentage point increase in ppFEV¬1 in subjects homozygous for F508del and a 7.02 mmol/L decrease in sweat chloride and 4.60 percentage point increase in ppFEV¬1 in subjects compound heterozygous for F508del and G551D from baseline through day 28 (P < 0.05 for all). CONCLUSIONS: These results support continued clinical development of tezacaftor 100 mg qday in combination with ivacaftor 150 mg q12h in subjects with CF. Clinical trial registration available at www.clinicaltrials.gov, ID NCT0153167.